Shaping Smartphone Purchase Decisions with Brand Image Analysis, Product Quality, and Compelling Prices - Hadi, Nur (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
This study aims to determine the influence of brand image, product quality and price on smartphone purchase decisions and also to find out and analyze the most dominant factors affecting Smartphone Purchase Satisfaction. In this study using a population of 9989 consumers according to PT. Bangga Teknologi Indonesia by using the Slovin formula obtained a sample of 100 respondents, the data analysis technique used is a quantitative associative method with a verifiative approach. The series of tests carried out are validity and reliability tests, classical assumption tests, simple linear regression analysis for simultaneous testing. The results prove that brand image has a positive and significant effect on smartphone purchase decisions that based on multiple generation tests of brand image, product quality and price simultaneously have a significant effect on purchasing decisions.